Analisis Dampak AI terhadap Model Bisnis Keuangan Syariah: Pendekatan Teknologi Informasi dan Etika - Amrizal Amrizal; Reza Fitriansyah; Herlini Herlini (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
The rapid evolution of information technology, particularly artificial intelligence (AI), has substantially transformed diverse sectors, including Islamic finance. This study aims to explore the impact of AI on Islamic finance business models, focusing on the interplay of technological integration and ethical considerations. Despite being in the early stages of technological adoption, AI demonstrates potential to enhance operational efficiency, minimize human error, and improve customer experiences. Data reveals that the global Islamic finance market reached USD 2.88 trillion in 2021; however, challenges persist in the integration of modern technologies. Employing qualitative research methods, in-depth interviews were conducted with 30 stakeholders in the Islamic finance sector to gather insights into the implications of AI. Findings indicate that AI can bolster risk analysis, personalize service offerings, and ensure compliance with Sharia principles, while raising important ethical and privacy concerns. This research contributes to a deeper understanding of how AI can reinforce Islamic finance business models in the digital age.